Remote monitoring of indoor/outdoor movement in epidemiological situations utilising UWB transceivers. (19th November 2021) - Rajendran, Sukumar; Jayagopal, Prabhu; Mathivanan, Sandeep Kumar; Prasanna, S.; Manivannan, S.S.; Kumar, P.J.; Venkatasen, Maheshwari; Mani, Prasanna
A global pandemic has reduced mobility, impacting the healthcare assessment, and diagnostics on co-morbid patients. Various challenges for location finding and indoor signalling issues give rise to the necessity for compact and low-cost ultra-wideband sensor technology. Lockdown has played a vital role during crisis in engaging with specific conditions like position estimation in areas under LOS and NLOS caused by diffraction and reflection of UWB signals across obstacles. UWB-based localisation system with edge/fog computing is used to analyse the indoor/outdoor usage of quarantined patients reducing the transmission, which becomes a threat for society and healthcare personals. The mathematical models to symbolise various patterns utilising UWB sensors with anchors and tags were used to determine the flow of all rapid and random movements within the specified clustered locations. The proposed system achieves high classification accuracy with SVM to classify the patterns and assist frontline medical workers in containing pandemics through human interaction.